Virtual reality simulation experiences in health assessment: a mixed-methods explanatory study examining student satisfaction and self-confidence - Vihos, Jill; Shah, Mamta; Chute, Andrea; Carlson, Susan (My University, 2024)
Background: Virtual reality simulations (VRS) have the potential for enhancing clinical preparation in undergraduate nursing education (Son et al., 2022). Researchers are examining the relationship between VRS experiences and learner outcomes (C hoi et al., 2022; Shah, Gouveia, Babcock, 2022). However, evidence from the adoption of VRS in laboratory courses is sparse. Aims: The purpose of this mixed-methods explanatory study was to explore the relationship between use of VRS and student satisfaction and self confidence in a health assessment laboratory (HA-L) course. Methods: 37 second-year students completed a postoperative respiratory distress scenario using Elsevier’s Simulation Learning System with Virtual Reality (SLS with VR). All participants completed the Satisfaction and Self-Confidence in Learning Scale (SSLS); a subset participated in one-to-one semi-structured interviews. Descriptive statistics and Spearman’s correlation coefficient were computed to assess the relationship between the ranked student satisfaction and self-confidence scores. Interview transcripts were analyzed using the Glaserian approach to identify themes and relationships between VRS experiences, student satisfaction and self-confidence. Results: Satisfaction and self-confidence scores were above average to high and found to be strongly correlated (rho (35) = 0.78, p < 0.0001). Fidelity, communication confidence and competence, learning with peers, integrated learning and critical thinking, and a safe space to learn were related to satisfaction and confidence. Conclusion and Implications: VRS experiences were correlated with high student satisfaction and self-confidence in a HA-L course; researchers should continue examining students’ experiences in VRS in additional laboratory courses.
Presented on June 12-15, 2024, at INACS24 Collaborate. Innovate. Grow, held at Raleigh Convention Center in Raleigh, NC.
Keywords: virtual reality simulators; learner outcomes; satisfaction and self-confidence; mixed-methods study; communication confidence